La gloria del simulacro: Enrique Rodríguez Larreta y la tradición castellana en Argentina (Revista de Crítica Literaria Latinoamericana, 2015)
"This paper analyzes the central role played by Argentinian modernista writer Enrique Rodríguez Larreta in the vindication of the Castilian cultural heritage in early 20th-century Argentina. As part of the wave of hispanophile sentiment produced by the Spanish-American War and the debates on identity linked to the celebration of Argentina’s Independence Centenary, Larreta aims to create a new Argentinian identity of Castilian filiation based on the Spanish cultural heritage epitomized by Golden Age. This profoundly conservative aesthetic project finds expression in his successful historic novel La gloria de don Ramiro, conceived as an archaist textual simulacrum that reconstructs the historical reality of Phillip II’s reign."
Keywords: Larreta; Modernismo; Simulacrum; National identity; Argentina